BANK SYARIAH DALAM PERSPEKTIF FILOSOFIS,YURIDIS DAN SOSIOLOGIS BANGSA INDONESIA - Supriyadi, Ahmad (IAIN Kudus, 2017)
Islamic bank is a financial institution that is essential for the people of Indonesia as an institution that is able to portray a welfare society with its products when it is implemented consistently. But the understanding of Islamic banks in the community is still in doubt because of Islamic bank same as conventional banks. Improper understanding of it can be explained by the philosophical, juridical and sociological.Islamic banking is a bank in its operations based on Islamic principles both in raising funds and mudaraba wadiah principles; in financing the purchase using the principles of Murabaha, salam and istishna; the issuing bank services products sharia apply the principle of al-wakalah,al-Hiwalah,al-qardh,al-kafalah, and al-Rahn. Three products when viewed legally has implemented of Constitution Number 21 concerning Islamic banking, and in a philosophical perspective in accordance with Pancasila, grand norm Constitution the 1945 and the Quran-Hadith, whereas in sociological perspective these principles have been entrenched in Indonesian society cooperation in agriculture